Removal of Cresols by Adsorption on Plastic Clay - Jaiswal, Mona; Maheshwari, A. (Asian Journal of Chemistry, 2010)
The adsorption of cresols (ortho, meta and para) on plastic clay has been investigated by means of a batch technique from their aqueous solutions. The effects of particle size and initial solute concentration have been studied and isotherm parameters are evaluated. The Freundlich Isotherm has been found to be more suitable for all the systems studied. Plastic clay is characterized with different analyses and has been found that silica and alumina are its major constituents responsible for adsorption. Thermomodynamic parameters are calculated.